Dome above the Mandapa of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The dome above the mandapa (pillared hall) of the Bhandasar Temple has two circles consisting of sixteen oval-shaped designs fashioned like mirrors. The outer or lower row has miraculous deeds from the life of Jain Acharyas, Dada guru Jinadatt Suri and Dada Guru Jinachandra Suri. The inner or upper row has stories from the lives of Rishabnatha Mahavir, Parshvanata and Neminath Tirthankaras.